2021
DOI: 10.1037/xhp0000771
|View full text |Cite
|
Sign up to set email alerts
|

Liking of art and the perception of color.

Abstract: Color has been a defining feature of paintings throughout art history. Despite the great diversity in the use of color between epochs, there are some surprisingly stable and unifying features in chromatic properties across visual artworks. For example, artists' palettes seem to be biased toward the yellow-red range of the spectrum. Here, we assess the impact of a holistic color manipulation (i.e., rotating the color gamut) on aesthetic liking and perceived colorfulness of abstract paintings. We presented 6 ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“… Nascimento et al (2017) found that viewers prefer the original colors in abstract paintings over rotated color versions, and found that artists’ color palettes throughout different epochs were dominated by the yellow-red range of the spectrum (cf. Altmann et al, 2021 , for related results). There has been a long tradition to believe that (all or at least most) people appreciate certain colors more than others, but there is also strong evidence that color preference has a lot to do with cultural background providing associations and a history of individual learning.…”
Section: Variables Affecting Image Aesthetics Of Mobile Phone Photogr...mentioning
confidence: 90%
“… Nascimento et al (2017) found that viewers prefer the original colors in abstract paintings over rotated color versions, and found that artists’ color palettes throughout different epochs were dominated by the yellow-red range of the spectrum (cf. Altmann et al, 2021 , for related results). There has been a long tradition to believe that (all or at least most) people appreciate certain colors more than others, but there is also strong evidence that color preference has a lot to do with cultural background providing associations and a history of individual learning.…”
Section: Variables Affecting Image Aesthetics Of Mobile Phone Photogr...mentioning
confidence: 90%
“…Another possible factor could be the perceived richness of colour (how many colours participants perceived). However, no evident correlation has been found between preference and colour richness; people do not simply prefer colourful paintings 20 . A recent study 23 focusing on the colour statistics of landscape paintings and photographs found significant correlations between colour statistics and visual aesthetics responses, although the authors tested only a limited number of images (15 paintings and 15 photographs).…”
Section: Introductionmentioning
confidence: 97%
“…These studies manipulated only colour composition by rotating the three-dimensional colour volume of unfamiliar paintings. Observers were asked to adjust the hue angle to obtain the best subjective visual impression 18 , to select their preference among pairs of hue-rotated versions of the same painting 19 , 21 , or to rate their personal evaluation of each original or hue-rotated painting presented 20 . Despite the minor differences in methodology, these studies commonly found that observers typically prefer a chromatic composition very close to the original, rather than one that is hue-rotated, even in the case of non-figurative or spatially scrambled paintings 19 , or patchwork images comprising different art paintings 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Since art paintings generally contain numerous colors, there is a tremendous gap between preferences for a single color and a range of colors, it seems futile to approach color preference in art paintings. However, more recent studies 45 47 have measured observers’ preferences for color composition by rotating the color gamut within the CIELAB color space. In these studies, observers were asked to adjust the hue angle of the color gamut of unfamiliar paintings to obtain the best subjective visual impression or to select the preferred one among pairs of hue-rotated versions of the same painting.…”
Section: Introductionmentioning
confidence: 99%